Webcam Based Fingerprint Authentication for Personal Identification System - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (2007)
In the networked world there are a huge number of systems that need biometric recognition, so at present it has become an important issue. For the personal identification various kinds of vision-based techniques have been proposed earlier. We present a novel one based on visual capturing of fingerprints using a webcam. Fingerprint image quality influences deeply the performance of fingerprint identification systems. This paper presents an improved authentication system using a low priced webcam as well as a preprocessing approach using gamma manipulation and gamma correction technique to adjust lightness and intensities of the fingerprint image due to enhance fingerprint image quality. We also implement and test our proposed approach using the FVC2004 database including the webcam database of 1200 fingerprint images which is obtained by proposed approach and compare the EER (Equal Error Rate), FRR (False Rejection Rate) and FAR (False Acceptance Rate) of each database. Experiment- al results show that our approach performs significantly improved and comparatively EER, FRR, FAR of the webcam database are very similar to the FVC2004 database.